Abnormal disclosure tone, earnings management and earnings quality. Issue 2 (6th January 2022) - Abou-El-Sood, Heba; El-Sayed, Dalia
Abstract : Purpose: The authors investigate whether abnormal tone in corporate narrative disclosures is associated with earnings management and earnings quality, in an emerging market context. Based on agency theory and opportunistic/impression management perspective, this study examines whether executives manage disclosure tone to support their opportunistic behavior, when using earnings management. Design/methodology/approach: This study uses a sample of earnings press releases of publicly traded firms in the MENA region during 2014–2019. It employs textual analysis to measure disclosure tone. The authors estimate abnormal disclosure tone after controlling for firm characteristics. Discretionary accruals proxy for earnings management and are estimated using Modified Jones model. Earnings quality is measured using accounting-based and market-based proxies: earnings smoothness, persistence, predictability and value relevance/informativeness. Findings: Results show a positive association between abnormal disclosure tone and earnings management. Additionally, results show that earnings persistence is higher for firms with lower levels of abnormal disclosure tone. Results are sustained for earnings smoothness, but not for predictability and value relevance/informativeness. Research limitations/implications: Results provide initial evidence of management's use of tone management jointly with earnings management. This adds to prior studies adopting the opportunistic perspective of disclosure tone, through showing that discretionary tone in narrative disclosures can be strategically used by management to influence investors' perceptions. Practical implications: The results provide valuable insight to board of directors, auditors and market participants on the possible biases emerging from tone of narrative disclosures in corporate reports. For regulators and standard-setters, results shed light on the need for regulations and rules beyond financial statements, to guide disclosure of narrative information in different corporate reports. Originality/value: This study contributes to the rare evidence that investigates textual disclosure characteristics to uncover management's opportunistic practices and assess earnings quality. Where majority of studies concentrate on developed markets, this study provides novel evidence of emerging markets by examining the association between abnormal disclosure tone and earnings management/earnings quality. Also, it validates the tone management model proposed by Huang et al . (2014) for capturing tone manipulation.